2006
DOI: 10.1017/s1481803500013981
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review of randomized controlled trials of therapeutic hypothermia as a neuroprotectant in post cardiac arrest patients

Abstract: Objective: Several randomized controlled trials have suggested that mild induced hypothermia may improve neurologic outcome in comatose cardiac arrest survivors. This systematic review of randomized controlled trials was designed to determine if mild induced hypothermia improves neurologic outcome, decreases mortality, or is associated with an increased incidence of adverse events. Science (1989 to November 2005. For each included study, references were reviewed and the primary author contacted to identify an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
34
0
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(39 citation statements)
references
References 62 publications
3
34
0
2
Order By: Relevance
“…Previous meta-analyses have used GOS (di chotomized into good [GOS score [4][5] or poor [GOS score [1][2][3]) as a simplified measure of neurologic outcome after TBI. [4][5][6][7] We also sought to determine whether there is a difference in the efficacy of shortterm cooling compared with a long-term or goaldirected strategy.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous meta-analyses have used GOS (di chotomized into good [GOS score [4][5] or poor [GOS score [1][2][3]) as a simplified measure of neurologic outcome after TBI. [4][5][6][7] We also sought to determine whether there is a difference in the efficacy of shortterm cooling compared with a long-term or goaldirected strategy.…”
Section: Methodsmentioning
confidence: 99%
“…Induced hypothermia is now an accepted measure to improve outcome following anoxic brain injury associated with cardiac arrest, [1][2][3] but its benefits in TBI are uncertain. Several older metaanalyses concluded that hypothermia is not effective for TBI.…”
Section: Overviewmentioning
confidence: 99%
“…18) It has been suggested that induction of hypothermia by AcAP would be effective for neuroprotection after cardiac arrest or stroke (therapeutic hypothermia). [19][20][21] It has also been reported that AcAP-induced hypothermia can be inhibited by genetic deletion of cyclooxygenase-1 15) (but see Li et al 16) ) and transient receptor potential ankyrin 1 (TRPA1). 14) While the importance of serotonin in the analgesic effect of AcAP has been suggested, the contribution of serotonin to AcAP-induced hypothermia has not been reported.…”
Section: 5)mentioning
confidence: 99%
“…9 In response, cooling was developed as a neuroprotection for ischemic cerebral tissues. Cheung et al 10 did systematic review of randomized controlled trials and found that despite differences in cooling protocols between the studies, the pooled results demonstrated that mild hypothermia is associated with statistically significant and clinically important decreases in hospital mortality and improvements in neurological outcome after cardiac arrest. 10 Despite the fact that TTM is a changing landscape, nursing care must continue to be delivered.…”
Section: Introductionmentioning
confidence: 99%